Digital Library with Disaster Mitigation Content to Enhance Elementary Students’ Reading Literacy and Environmental Care - Nurul Istiq'faroh; Suryanti Suryanti; Hendratno Hendratno; Rosniwaty Rosniwaty; Amiruddin Hadi Wibowo; Nico Irawan (Universitas Muhammadiyah Surakarta, 2026)
This study examined the effectiveness of a digital library featuring illustrated stories with disaster mitigation content in enhancing reading literacy and environmental care among elementary students. The programme addressed the issue of a lack of individuals possessing adequate reading and writing skills, while concurrently emphasising the significance of imparting environmental education to children from an early age, a particularly salient consideration in regions such as Indonesia, where there is a high incidence of natural disasters. The present study employed a quantitative one-group pretest–posttest design, with 30 fourth-grade students (aged 9–10 years) being selected through purposive sampling. The instruments comprised a reading literacy test and a Likert-scale measure of attitudes towards environmental care. Due to non-normal distribution, data were analysed using the Wilcoxon signed-rank test. The results revealed significant improvements in reading literacy and environmental care attitudes, with all students achieving positive ranks. There were no declines recorded, and positive effects were evident in terms of students’ enthusiasm, active participation, and ability to connect stories with real-life disaster experiences. These results show that combining digital illustrated stories with disaster mitigation content is an effective way to support literacy development, character education and environmental awareness.